Sources of income as a factor of interregional socio-economical differentiation of Russian population (1995 - 2007 YEARS) - Irina Gerasimova (European Regional Science Association (ERSA), 2010)
The principal results of the statistical and econometrical studying of dynamics and factors of income inequality across the regions of The Russian Federation (RF) during 1995 - 2007 years have been presented at the paper. The objects of investigation have been the 79 subjects of RF. They have been described by variables: (a) population; (b) income per capita (at average for all population, living at the subject); (c) structure of income: the share of total income, obtained at average of all people in subjects, by five sources (their sum is equal to 100%): (1) business (enterprise) activity; (2) wages (salaries); (3) social transfers; (4) property; (5) other incomes. As the first step of "space - time" analysis dynamics and differentiation of seven named above indicators have been studied. The same initial indicators let us to estimate Total Monetary Income (TMI) and its five component TMI(k), k=1, . . .,5 for each from 79 regions of RF. The spatial distributions of new six variables and their evolution from beginning of transition up to crisis have been considered at the second step of investigation. The GINI and FUND coefficients have been calculated for TMI and for its five components. The subjects of TMI concentration have been determined by comparative level-dynamic analysis of these indicators. The same has been done for TMI(k) from five sources. It could say that practically each region of RF has had the different way of social - economic development. GINI decomposition by five sources of income, presented GINI as a linear combination of income structure and the Coefficients of Concentration, has been the next step of investigation. The results of decomposition indicated clear that two sources of income - (4) "properties" and (5) "other incomes" have been the main factors of interregional income inequality. There are "short lists" of subjects of RF, where the incomes from these two sources have been concentrated. The Decomposition method let us to discuss the different aspects of income inequality and make the emphasis at institutional factors of population economic activities and income redistribution.
Keywords: 330; Russia; regions; income per capita; sources of incomes; structure ofincome; spatial inequality; GINI; coefficient of Concentration; decomposition